(untitled) (Journal of Dhaka Medical College, 2015)
The study was carried out to evaluate the fate and outcome of eclampsia patients and their neonates. This hospital based prospective study was done in Chuadanga Sadar Hospital, a 100 bed secondary health care centre in Chuadanga district in Bangladesh, from January 2007 to December 2009. The number of study population was 50, which include antepartum, intrapartum and postpartum eclampsia. Among them, 70% had spontaneous vaginal delivery, 10% had assisted vaginal delivery and 10% had caesarian section. 86% of the patient have good maternal outcome with the use of anti convulsant therapy. 46% of baby of total population have good neonatal outcome with or without immediate resuscitation. The outcome of eclampsia is satisfactory if immediate treatment is started. Hence, every patient should be admitted in hospital as soon as possible and receive anticonvulsant therapy immediately, even before admission in hospital. Patient should be delivered with special care as a high risk mother and neonatal support should be given to reduce both maternal and neonatal mortality and morbidity. J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 223-226